Nutritional Status and Diarrhea in Toddlers Aged 0 – 59 Months - Kantri, Wafa Afrodita; Harahap, Roito Elmina Gogo; Budiman, Muhamad Arif (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2022)
Background: Diarrhea is one of the diseases that ranks in the top ten diseases in Depok City. Data from the Depok City Health Service (2020) states that diarrhea in toddlers is still above 5%. There are various factors (multifactor) related to diarrhea disease, one of which is nutritional status. Purposes: Our study aims to analyze the relationship between nutritional status and diarrhea in toddlers in the Pancoran Mas District Health Center. Methods: We used an observational analytic method with a cross-sectional approach on 396 toddlers aged 0 – 59 months. This research was conducted from October 2021 – March 2022. The type of data in this study is secondary data taken through medical records and analyzed using the chi-square test. Result: The prevalence of low-poor nutritional status was 38,9%, the prevalence of diarrhea was 21,2%, and the results of the chi-square analysis between diarrhea and nutritional status obtained p value = 0.334. Conclusion: Incidence of diarrhea in Depok City is still relatively large. There are many other factors that associated with the incidence of diarrhea such as personal hygiene, environmental hygiene and various other factors.